Addressing Load Factor Issues at BIJB Airport: Critical Factors in Mode Selection and Airport Choice - Karno Kinasih, Reni; Isradi, Muhammad; Nabila; Indriany, Sylvia; Biantoro, Agung Wahyudi; Putri, Mukhlisya Dewi Ratna (Recent Trends in Civil Engineering and Built Environment, 2025)
The West Java International Airport (BIJB) Kertajati was designed to alleviate passenger congestion at the Husein Sastranegara Airport in Bandung. Despite its capacity to serve 5.6 million passengers annually, BIJB has experienced low occupancy rates since its inauguration in 2018. This study investigates the factors influencing passengers' decisions to use BIJB Kertajati, focusing on issues such as airfare, baggage fees, limited flight routes, and the airport's accessibility. The research evaluates the impact of the Cisumdawu Toll Road on airport preference and explores demographic factors, including profession, income, and travel purpose. Data was collected via surveys from five key cities in West Java's catchment area, and statistical analysis, including the Chi-Square Test of Independence, was used to assess relationships between variables. Results indicate that fare policies, accessibility, and travel purposes significantly affect airport choice. The study concludes that improving infrastructure, reducing airfares, and increasing flight frequency could enhance BIJB's load factor, making it a more competitive option for travelers in the region